BRCA1 is Expressed in Uterine Serous Carcinoma (USC) and Controls Insulin-Like Growth Factor I Receptor (IGF-IR) Gene Expression in USC Cell Lines. Issue 5 (1st June 2012) - Amichay, Keren; Kidron, Debora; Attias-Geva, Zohar; Schayek, Hagit; Sarfstein, Rive; Fishman, Ami; Werner, Haim; Bruchim, Ilan
Abstract : Objective: The insulin-like growth factor I receptor (IGF-IR) and BRCA1 affect cell growth and apoptosis. Little information is available about BRCA1 activity on the IGF signaling pathway. This study evaluated the effect of BRCA1 on IGF-IR expression. Methods: BRCA1 and IGF-IR immunohistochemistry on archival tissues (35 uterine serous carcinomas [USCs] and 17 metastases) were performed. USPC1 and USPC2 cell lines were transiently cotransfected with an IGF-IR promoter construct driving a luciferase reporter gene and a BRCA1 expression plasmid. Endogenous IGF-IR levels were evaluated by Western immunoblotting. Results: We found high BRCA1 and IGF-IR protein expression in primary and metastatic USC tumors. All samples were immunostained for BRCA1—71% strongly stained; and 33/35 (94%) were stained positive for IGF-IR—2 (6%) strongly stained. No difference in BRCA1 and IGF-IR staining intensity was noted between BRCA1/2 mutation carriers and noncarriers. Metastatic tumors stained more intensely for BRCA1 than did the primary tumor site ( P = 0.041) and with borderline significance for IGF-IR ( P = 0.069). BRCA1 and IGF-IR staining did not correlate to survival. BRCA1 expression led to 35% and 54% reduction in IGF-IR promoter activity in the USPC1 and USCP2 cell lines, respectively. Western immunoblotting showed a decline in phosphorylated IGF-IR and phosphorylated AKT in both transiently and stably transfected cells. Conclusions: BRCA1 and IGF-IR are highly expressed in USC tumors. BRCA1 suppresses IGF-IR gene expression and activity. These findings suggest a possible biological link between the BRCA1 and the IGF-I signaling pathways in USC. The clinical implications of this association need to be explored.